Europeanization, actor constellations and spatial policy change in Greece. - Giannakourou, Georgia (TH Zürich, NSL, 2011)
Der Beitrag untersucht den Einfluss der EU auf die räumliche Planung in Griechenland, in dem er sich vor allem auf die Rolle der einheimischen Akteure im Prozess der Europäisierung konzentriert. Die Autorin identifiziert die Schlüsselakteure in den Reformprozessen der räumlichen Planungssysteme und untersucht die Rolle epistemischer Gemeinschaften seit dem Beginn der 1990er Jahre. Sie kann bei der Untersuchung auch auf unveröffentlichtes Material zurückgreifen.

This article seeks to analyze EU influence on Greek planning by focusing on the role of domestic actors implicated in the process of Europeanization. It aims to examine the key agents involved in planning reforms, systematize the major discourses in the policy-process and explore the core instruments used as well. Linking key literature to first-hand information (legal documents, case-law, speeches, unpublished committees' reports and conference proceedings) and eye-witness accounts, the paper attempts to highlight the role of both strategies and ideas in different episodes of Europeanization of Greek spatial planning.
Keywords: Raumplanung; Planungssystem; Planungsorganisation; Raumplanungsbehörde; Raumplanungsinstitution; Planungspraxis; Planungsinstrument; Raumplanungspolitik; Europäisierung; Planungskultur; Raumplanungshoheit; Raumplanungsprogramm; Akteur; Akteursforschung; Territoriale Agenda der EU; Territoriale Governance; Governance; Planungsgeschichte; Politikforschung